PROBLEMATIKA KURANGNYA MEDIA PEMBELAJARAN DI SD TANJUNGSARI YANG BERDAMPAK PADA KETIDAK EFEKTIFAN PADA PROSES PENILAIAN - Qomariyah, Ryzca Siti; Karimah, Inayatul; Masruro; Soleha, Rita; Ferdiansyah, Dandi (PARAMETER: Jurnal Pendidikan Universitas Negeri Jakarta, 2022)
Learning media is a means of influencing a teaching and learning process. In the absence of learning media, it is difficult for KBM to be implemented effectively. Without realizing it, learning media has an important role in addition to teachers and students as the main objects in the learning process. In this case it can be concluded that if the learning media is minimal/less then it will hinder the creation of real educational goals. Besides that, the full contribution of the school is also very much needed in creating competent teachers in order to be able to form a conducive and enjoyable student learning enthusiasm that can get encouragement in increasing student motivation in learning. The effectiveness of the assessment is also necessary in the teaching and learning process, because with the assessment the teacher can determine the abilities of each individual/student. Assessment does not only focus on the learning outcomes that have been obtained, but also on the process of how students learn. Assessment also functions as a relationship that influences each other and there is reciprocity between students and teachers, assessment in education also aims to find out the increase in student learning activities, in order to improve and enhance student learning at school and at home. Problems that often occur related to learning media usually occur in schools located in remote areas, which are far from the reach of the government. It can be exemplified by the lack of supply of textbooks and infrastructure such as projectors, etc. that can support success in learning. In this case students have difficulty finding learning resources, so the teacher must contribute to creating learning media to cover these deficiencies, because the teacher has a very big role in changing student learning. Abstrak Media pembelajaran merupakan sarana berpengaruh pada suatu KBM. Tidak adanya media pembelajaran, KBM sulit untuk terselenggara secara efektif. Tanpa disadari, media pembelajaran memiliki peran penting disamping guru dan siswa sebagai objek utama dalam proses belajar. Dalam hal ini dapat disimpulkan bahwasanya jika media pembelajaran minim/kurang maka akan menghambat terciptanya tujuan pendidikan yang sesungguhya. Disamping itu kontribusi penuh pihak sekolah juga sangat dibutuhkan dalam menciptakan guru yang kompeten guna dapat membentuk semangat belajar siswa yang kondusif dan menyenangkan yang dapat memperoleh dorongan dalam meningkatkan motivasi siswa dalam belajarnya. Keefektifan penilaian juga perlu dalam proses KBM, karena dengan adanya penilaian guru dapat mengetahui kemampuan tiap individu/siswa. Penilaian bukan hanya fokus dengan hasil belajar yang telah didapatkan, tetapi juga pada proses cara belajar yang dilakukan siswa. Penilaian juga berfungsi sebagai hubungan yang saling mempengaruhi dan adanya timbal balik antara siswa dengan guru, penilaian dalam pendidikan juga bertujuan mengetahui peningkatan kegiatan belajar siswa, guna memperbaiki dan meningkatan belajar siswa disekolah maupun dirumah. Problematika-problematika yang sering terjadi terkait dalam media pembelajaran biasanya terjadi di sekolah-sekolah yang terletak di pedalaman, yang jauh dari jangkauan pemerintah. Dapat dicontohkan seperti kurangnya pasokan buku paket serta sarana prasarana seperti proyektor dll yang dapat menunjang keberhasilan dalam pembelajaran. Dalam hal ini peserta didik mengalami kesulitan untuk menemukan sumber belajar, sehingga guru harus berkontribusi untuk menciptakan media pembelajaran untuk menutupi kekurangan tersebut, karena guru memiliki peran yang sangat besar untuk perubahan peserta didiknya.